Dynamic compressive behaviour of spiral steel fibre reinforced concrete in split Hopkinson pressure bar tests - Hao, Yifei; Hao, Hong (Elsevier BV, 2013)
It has been well demonstrated that adding fibres into concrete increases the impact loading resistance capacity of the concrete material. Recent studies proved that using spiral-shaped steel fibres further increases the post-failure, energy absorption and crack stopping capacities of concrete as compared to other conventional steel fibres because spiral-shaped fibre better bonds in the concrete matrix and has larger deformation ability. This research further investigates the dynamic compressive properties of spiral fibre reinforced concrete (SFRC) by conducting high rate impact tests using split Hopkinson pressure bar (SHPB). SFRC specimens with different volume fractions of spiral fibres ranging from zero to 1.5% are prepared and tested. The concrete matrix for all SFRC specimens is mixed to obtain a compressive strength of 35 MPa. The influences of different volume fractions of fibres on strength, Young's modulus, stress-strain relationand energy absorption of SFRC specimens under quasi-static and dynamic loadings are studied. In dynamic compression tests, the strain rate achieved ranges from 50 s-1 to 200 s-1. The failure processes and failure modes of SFRC specimens with different fibre volume fractions are captured by the high speed camera during the tests and compared. Dynamic stress-strain curves under different strain rates are derived. The energy absorption capacities of the tested specimens are obtained and compared. Rate effects on the compressive strength and Young's modulus are also discussed. The corresponding empirical DIF (dynamic increase factor) relations for spiral SFRC are proposed.